Institutional Example as a Pillar of Character Formation of Muslim Student at Tadika Perpaduan Malaysia - Ahmad Nursalim; Rizkan Abqa (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
The study purpose was to examine the role of institutional role modeling in shaping the character of Muslim students at Tadika Perpaduan Batu Lancang, Penang, Malaysia, by analyzing the relationship between institutions, institutional culture, and the school environment based on Islamic education principles. The research used a qualitative descriptive method with a field study approach. Data were collected through observations and interviews conducted by students involved in the Community Service Program (KPM) and the International Teaching Practice Program (PPL) of STIT Al Washliyah Central Aceh.The results show that institutional role modeling plays a strategic role in integrating spiritual and social values into the educational process. Strong synergy between institutional leadership, organizational structure, and school culture contributes significantly to effective character formation among Muslim students. The study concludes that institutional role modeling is essential in developing the character of Muslim students from an early age. Strengthening institutional culture and exemplary leadership can enhance Islamic character education and support students in responding to technological and social challenges.